Persepsi Dukungan Supervisor Sebagai Pemoderasi Pada Pengaruh Workplace Bullying Terhadap Turnover Intention - Merdiana, Candra Vionela; Gumelar, Bagus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
One of the fundamental problems in an organization or company is the employee's desire or intention to leave (turnover intention). The high desire of employees to leave their workplace can be caused by many factors, one of which is workplace bullying, in addition, supervisor support can also weaken or strengthen the influence of workplace bullying on turnover intention. The aim of this research is to examine and analyze perceptions of supervisor support as a moderating variable on the influence of workplace bullying on turnover intention among security employees. This kind of study employs survey techniques and is quantitative in nature. The participants in this study were all of the security personnel at an educational institution in Yogyakarta, totaling 140 employees, while the sample was some of the security employees of an educational institution in Yogyakarta. The sample strategy employed in this study was non-probability sampling with the Incidental sample approach. The unit of analysis is the individual, namely the security employee. For instrument testing, this research uses tests for reliability and validity as requirements the multiple regression analysis approach is utilized to test the hypothesis after it has been the direct effect and also the moderating effect using the interaction test or Moderate Regression Analysis (MRA). The outcomes of a hypothesis test using multiple regression analysis showed that the initial hypothesis was rejected, namely that the influence of workplace bullying did not have a major impact on the intentions of turnover, while the second hypothesis was also declined, specifically that supervisor support did not moderate the influence of workplace bullying on turnover intentions.